Deep radiomics: a picture’s worth a thousand words - a review - Meraj, Syeda; Shah, Asadullah; Ismail, Ahsiah; Tengku Sembok, Tengku Mohd; Shadab, Syed; Aftab, Syed; Nageena, Syeda; Khan, Nusratullah; Nusratullah, Kajal (IEEE, 2024)
Abstract—In recent decades, the prevalence of diseases has witnessed a notable surge. The increasing health challenges have led to a greater use of advanced diagnostic machines for detecting and understanding these disease conditions. The diagnostic modalities, such as X-rays, CT scans, MRI scans, and nuclear medicine imaging, generate a wealth of interpretative data through medical images. Deep Radiomics aims to improve the efficiency and accuracy of image interpretation by automating the process of feature extraction, allowing for more comprehensive insights for advancing personalized medicine and improving outcomes in medical imaging. Enhance disease detection, diagnosis, and subsequent treatment strategie